Pelatihan Pemanfaatan Internet di Bidang E-Commerce dalam Meningkatkan Keahlian SDM Komunitas Wisata Baluwarti Solo: - - Budiningtyas, RR. Erna Sadiarti; Zayid Musiafa; Vivi Monita; Tutus Praningki (Universitas Muhammadiyah Surakarta, 2024)
The Baluwarti Tourism Community is a community that engages in tourism, spa therapy services, herbal medicine, culinary, and textile-fashion. The community has the potential to utilize technology for marketing and sales. However, the Baluwarti Tourism Community has not yet utilized e-commerce for marketing. This community service activity aims to improve the skills of the Baluwarti Tourism Community's human resources in marketing their products through e-commerce. The activity was carried out in three stages: preparation, mentoring, and evaluation. The results of the activity showed that members of the Baluwarti Tourism Community experienced an increase in skills in the field of digital-based technology, especially in the use of e-commerce. In addition, the activity also succeeded in building a partnership between the Baluwarti Tourism Community and UPITRA University. In conclusion, this community service activity has successfully achieved its goals. The activity has improved the skills of the Baluwarti Tourism Community's human resources in marketing their products through e-commerce, building partnerships, and sustainability.